P236 Cardiovascular risk following the use of long-acting bronchodilators of the UK's asthma population: a nested case-control study. (12th November 2019) - Almazrua, AA; Sundaram, V; Quint, JK; Bloom, CI
Abstract : Introduction: Recently, Wang et al (JAMA, 2018) examined cardiovascular risk following the use of certain inhalers, specifically in incident users of long-acting beta-agonists (LABA) and long-acting antimuscarinic antagonists (LAMA) in an adult Chronic Obstructive Pulmonary Disease (COPD) population. These drugs are increasingly used in asthma patients and we sought to determine whether LABA may raise the risk of cardiovascular disease in patients with asthma in the UK. Methods: Data was derived from primary care records (Clinical Practice Research Datalink) linked to secondary care database (Hospital Episodes Statistics), from January 2004 until January 2017. A cohort of LABA-LAMA naïve asthma patients were identified from which a nested case-control (ratio of 1:4) were matched on age, sex and GP practice was utilised. The outcome was cardiovascular disease (CVD; ischaemic heart disease (IHD), stroke, heart failure, hypertension or arrhythmias). The primary exposure was LABA prescriptions in the year prior to the date of CVD or equivalent date for the controls. A conditional logistic regression was applied to estimate the association between LABA use and CVD. LABA use was classified into current (<30 days), recent (31–90 days), old (91–180 days) and remote (181–365 days) use. Current users were further categorised into 'incident' users (no prescription preceding the 30 days) and 'prevalent' users (prescriptions including and prior to the preceding -30 days). Results: 357, 300 asthma patients were identified of which 13, 868 cases and 55, 472 controls were eligible for the study. The mean age was 63.9 years, 55% were female. Incident LABA use was associated with 1.62-fold (95% CI, 1.17–2.24, P<0.05) increased odds of CVD, whereas prevalent LABA use had an absent risk, after adjusting for BMI, smoking status, asthma severity, and a history of atopy, COPD, pneumonia, pulmonary embolism, asthma exacerbations, depression, anxiety, GERD, stroke, IHD, heart failure, cardiac arrhythmias, hypertension and cardiac medications. Conclusion: Incident, but not prevalent, LABA use was associated with an increased risk of CVD in asthma patients irrespective of prior CVD status or asthma severity.